Creating incentives for gender integration in livestock and fish research - Randolph, Thomas F. (International Livestock Research Institute, 2016)
Tom Randolph highlights how researchers are incentivized to take up gender as an important component of their research. Once they define a project with a gender component, they can receive financial support to implement the project or get backstopping by a gender specialist. Scientists are encouraged to understand gender dynamics in their field and become “gender fellows”. Publishing the research outcomes is valuable and demanded by the market. Scientists can benefit professionally by engaging in gender-related activities. Interview with Thomas F. Randolph (CGIAR Research Program on Livestock and Fish) for the book "A different kettle of fish? Gender integration in livestock and fish research". http://hdl.handle.net/10568/76684